Procurement Principles and Management - Baily, Peter (New York Prentice Hall Financial Times, 2008)
Previously entitled 'Purchasing Principles and Management' this book has been essential reading and the standard text for practitioners and students of the subject of purchasing or procurement for nearly 40 years. This new tenth edition continues to cover the continuous change and development in the field of Purchasing and care is taken to balance new emerging philosophies with the proven and established thinking and practice in the profession. This book will provide the reader with a reflection of sound mainstream practice combined with comment and insight into developing ideas and approaches. This edition includes: New chapters on outsourcing, corporate social responsibility and e-procurement systems, Well-integrated new material on time compression, global sourcing and contract performance measurement, New case studies plus mini-cases dotted throughout chapters to reflect themes from the text in actual supply management practice around the world, New Research boxes within chapters to link academic research and procurement industry practice, New PowerPoint Slides and an Instructor's Manual for Lecturers teaching the subject
Includes bibliographical references and index.
Keywords: Purchasing-Management.Industrial procurement-Management.